Complex Endodontic Treatment of Dens Invaginatus Type III in Maxillary Lateral Incisor: Reports of Two Cases (BIRDEM Medical Journal, 2016)
Dens invaginatus is a developmental malformation of teeth, showing a wide spectrum of anatomical variations, resulting from the invagination of a portion of a crown that might be confined to the crown or it may pass the cement-enamel junction and may result in a second apical foramen formation during the stage of odonto-genesis. It is clinically significant due to early development of caries and subsequent necrosis of the pulp. Chronic peri-apical lesions are often associated with these anomalies without clinical symptoms. Clinicians should be mindful of the possibility of dens invaginatus when a patient comes with a tooth having signs of pulpitis without history of trauma, caries and should examine the suspicious tooth as well as the peri-odontium radiographically. Most affected permanent teeth are the maxillary lateral incisors followed by central incisors, canines, premolars and molars. This article describes both surgical and nonsurgical endodontic management of dens invaginatus type III with large apical radiolucency in upper left lateral incisorBirdem Med J 2015; 5(2): 111-115